2018
DOI: 10.1093/cid/ciy964
|View full text |Cite
|
Sign up to set email alerts
|

Measles Immunity at 4.5 Years of Age Following Vaccination at 9 and 15–18 Months of Age Among Human Immunodeficiency Virus (HIV)–infected, HIV-exposed–uninfected, and HIV-unexposed Children

Abstract: BackgroundHuman immunodeficiency virus (HIV)–infected and HIV-exposed–uninfected (HEU) children may be at increased risk of measles infection due to waning of immunity following vaccination. We evaluated persistence of antibodies to measles vaccination at 4.5 years of age in HIV-unexposed, HEU, and HIV-infected children with CD4+ ≥25% previously randomized to immediate antiretroviral therapy (ART) interrupted at 12 months (HIV/Immed-ART-12), 24 months (HIV/Immed-ART-24), or when clinically/immunologically indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Two doses of measlescontaining vaccine administered at 6 and 12 months of age were shown to be similarly safe and immunogenic in HIVunexposed and HIV-exposed, uninfected children [87]. However, HIV-infected children and adolescents may need additional MMR vaccine doses to achieve sufficient levels of immunity, especially if antiretroviral therapy has been interrupted [88]. MMR vaccination may also be considered in patients with other immune deficiencies for whom the benefits of vaccination outweigh the risks, such as patients with immunoglobulin G (IgG) subclass deficiencies, congenital neutropenia, chronic granulomatous disease, and complement deficiency diseases [86].…”
Section: Unvaccinated or Under-vaccinated Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two doses of measlescontaining vaccine administered at 6 and 12 months of age were shown to be similarly safe and immunogenic in HIVunexposed and HIV-exposed, uninfected children [87]. However, HIV-infected children and adolescents may need additional MMR vaccine doses to achieve sufficient levels of immunity, especially if antiretroviral therapy has been interrupted [88]. MMR vaccination may also be considered in patients with other immune deficiencies for whom the benefits of vaccination outweigh the risks, such as patients with immunoglobulin G (IgG) subclass deficiencies, congenital neutropenia, chronic granulomatous disease, and complement deficiency diseases [86].…”
Section: Unvaccinated or Under-vaccinated Individualsmentioning
confidence: 99%
“…Therefore, concerns of possible waning immunity after MMR vaccination has been proposed as a key contributing factor to mumps resurgence, especially in highly vaccinated populations [3,26,152,155,156]. Waning immunity for measles has been well-established in HIV-infected children, in particular if antiretroviral therapy has been interrupted [88]. For rubella, previous studies have shown that following two doses of MMR vaccine during childhood, the seropositivity rates remained high in young adults but antibody concentrations declined below protective levels in some individuals, which could have implications for the prevention of rubella in pregnancy [157][158][159].…”
Section: Secondary Vaccination Failurementioning
confidence: 99%
“…The seroconversion rate after two doses of the vaccine is around 96%, but there is a slow decline in seroprotection even in healthy children [11]. A greater degree of reduced immunity against measles has been documented in children with malignancies, kidney transplantation, and HIV infection [12][13][14][15]. However, there is little evidence for the same in children with DTNS.…”
Section: Introductionmentioning
confidence: 99%